PERUBAHAN LEGITIMASI PENUNTUTAN MILITER DI INDONESIA (Studi Kasus Pembentukan Jaksa Agung Muda Pidana Militer di Kejaksaan RI) - Febrina Rahmawati (2022)
Military institutions throughout the country have a special judicial mechanism known as military justice. Judicial jurisdiction does not look at criminal acts based of the perpetrator, but based on the offense or crime committed. The formation of the organizational structure and working procedures of the Deputy Attorney General for Military Crime (Jampidmil) at the Indonesian Attorney General's Office can bridge the need for criminal prosecution of subjects of civil law and subjects of military law. This study aims to describe the change in the legitimacy of military prosecution in Indonesia with the establishment of a new work unit at the Indonesia Attorney General's Office, namely the Deputy Attorney General for Military Crimes. The type of research used is normative juridical. This research focuses on laws relating to the structure and how the process or procedures for enforcing military law in the military prosecution system